1990
DOI: 10.1161/01.str.21.5.801
|View full text |Cite
|
Sign up to set email alerts
|

Collagenase-induced intracerebral hemorrhage in rats.

Abstract: Intracranial bleeding is an important cause of brain masses and edema. To study the pathophysiology of intracerebral hemorrhage, we produced experimental hemorrhages in 53 rats and characterized the lesion by histology, brain water content, and behavior. Adult rats had 2 fil saline containing 0.5 unit bacterial collagenase infused into the left caudate nucleus. Histologically, erythrocytes were seen around blood vessels at the needle puncture site within the first hour. By 4 hours there were hematomas, the siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
386
0
7

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 537 publications
(398 citation statements)
references
References 30 publications
5
386
0
7
Order By: Relevance
“…Bacterial collagenase model: Injection of bacterial collagenase into the basal ganglia of rats to breakdown the basal lamina of blood vessels was first introduced in the early 1990s (Clark et al, 1998;Rosenberg et al, 1990). In the collagenase model, bleeding begins around 10 minutes after injection, but develops slowly into a full hematoma 4 to 24 hours later (Rosenberg et al, 1990).…”
Section: Autologous Blood Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial collagenase model: Injection of bacterial collagenase into the basal ganglia of rats to breakdown the basal lamina of blood vessels was first introduced in the early 1990s (Clark et al, 1998;Rosenberg et al, 1990). In the collagenase model, bleeding begins around 10 minutes after injection, but develops slowly into a full hematoma 4 to 24 hours later (Rosenberg et al, 1990).…”
Section: Autologous Blood Modelmentioning
confidence: 99%
“…In the collagenase model, bleeding begins around 10 minutes after injection, but develops slowly into a full hematoma 4 to 24 hours later (Rosenberg et al, 1990). An advantage of this simple and reproducible model is that the hemorrhage occurs from in situ vessels (Wang and Tsirka, 2005), and it may imitate hematoma expansion (the bleeding-rebleeding phenomenon).…”
Section: Autologous Blood Modelmentioning
confidence: 99%
“…We adapted the collagenase-induced ICH model (Rosenberg et al, 1990) previously described in mice (Choudhri et al, 1997;Clark et al, 1998). Briefly, mice were anesthetized with an intraperitoneal injection of ␣-chloralose (40 mg/kg) and urethane (400 mg/kg) and positioned prone in a stereotaxic head frame (Stoelting, Kiel, WI, U.S.A.).…”
Section: Intracerebral Hemorrhage Inductionmentioning
confidence: 99%
“…Previous studies have reported traumatic brain injury with models such as injections of autologous blood, balloon distension, inertial acceleration, force impact and cold (Finnie and Blumberg, 1990). Rosenberg et al (1990) have established the collagenase-induced intracerebral hematoma model, which is highly reproducible and shows many characteristics of the intracerebral hemorrhagic process in mammals. Only one recent paper has shown that collagenase-induced thalamic lesions can cause central pain in rats (Wasserman and Koeberle, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Since most analgesics have anti-inflammatory properties (Ferland et al, 2007), no analgesics were administered postoperatively since this could change the outcome of the study. We also wanted to reproduce the Rosenberg model in which no analgesic is administered either pre-or post-operatively (Rosenberg et al, 1990).…”
Section: Surgical Methodsmentioning
confidence: 99%